2015
DOI: 10.1080/17470218.2015.1032986
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Communication: Personality and attention: Levels of neuroticism and extraversion can predict attentional performance during a change detection task

Abstract: The present study demonstrates that levels of extraversion and neuroticism can predict attentional performance during a change detection task. After completing a change detection task built on the flicker paradigm, participants were assessed for personality traits using the Revised Eysenck Personality Questionnaire (EPQ-R). Multiple regression analyses revealed that higher levels of extraversion predict increased change detection accuracies, while higher levels of neuroticism predict decreased change detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 21 publications
4
24
0
Order By: Relevance
“…This view is supported by our finding that higher extraversion was associated with lower heart rate, such that lower autonomic arousal might have underpinned poorer retrieval performance (Geen, 1984;Harvey & Hirschmann, 1980). Notably, the relationship between arousal and performance determines how different levels of arousal match optimal task environments: Overall, extraverts may not generally perform worse than introverts on cognitive tasks, but are more likely to outperform introverts in fast-paced (Hahn et al, 2015), sensory stimulating environments (Geen, 1984), arguably since higher task demand increases extraverts' cortical (Fink et al, 2005;Kumari et al, 2004) and autonomic arousal (Geen, 1984;Harvey & Hirschmann, 1980) to drive optimal performance. The fact that our retrieval task was slow-paced (three second responses) and carried out in a quiet lab environment could have contributed to extraversion-related retrieval deficits.…”
Section: Cardiac Influences On Associative Retrieval As a Function Ofmentioning
confidence: 61%
See 1 more Smart Citation
“…This view is supported by our finding that higher extraversion was associated with lower heart rate, such that lower autonomic arousal might have underpinned poorer retrieval performance (Geen, 1984;Harvey & Hirschmann, 1980). Notably, the relationship between arousal and performance determines how different levels of arousal match optimal task environments: Overall, extraverts may not generally perform worse than introverts on cognitive tasks, but are more likely to outperform introverts in fast-paced (Hahn et al, 2015), sensory stimulating environments (Geen, 1984), arguably since higher task demand increases extraverts' cortical (Fink et al, 2005;Kumari et al, 2004) and autonomic arousal (Geen, 1984;Harvey & Hirschmann, 1980) to drive optimal performance. The fact that our retrieval task was slow-paced (three second responses) and carried out in a quiet lab environment could have contributed to extraversion-related retrieval deficits.…”
Section: Cardiac Influences On Associative Retrieval As a Function Ofmentioning
confidence: 61%
“…Lastly, we predicted a modulatory influence of personality on emotion-related associative learning and memory reinforced at specific cardiac timings. Extraverts reportedly perform better in stimulating ('high arousal') environments, evidenced by better performance, relative to introverts, on fast-paced change detection tasks (Hahn, Buttaccio, Hahn, & Lee, 2015) and on associative learning tasks in acoustically noisy contexts (Geen, 1984). We therefore predicted that extraverts would show improved learning and/or retrieval of face-name pairs reinforced at systole as a result of enhanced cardiovascular arousal.…”
Section: The Present Studymentioning
confidence: 97%
“…1). Another potential mechanism connecting personality with attention resides in affective states because affective states influence the items to which an individual attends in a scene and for how long (Hahn et al 2015). Although such relationships present opportunities for better linking personality with accidents, lingering uncertainties about the personality elements that best predict the at-risk behaviors that have been considerably understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Visually impaired subjects with high neuroticism had also a lower cognitive score than those with a low neuroticism level. Others [59][60][61] found that neuroticism was associated with decreased attentional control over the visual field, and it was proposed that neuroticism decreased attentional disengagement. We showed that lower neuroticism correlated significantly with vision recovery, but a prospective study with a larger sample should establish the cause-effect relationship.…”
Section: Personality and Vision Recoverymentioning
confidence: 99%